2009
DOI: 10.1002/jclp.20597
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and mental disorder

Abstract: Emotional abilities were measured with a performance test of emotional intelligence (The Mayer-Salovey-Caruso Emotional Intelligence Test; Mayer, Salovey, & Caruso, 2002) in patients diagnosed with major depressive disorder, substance abuse disorder, or borderline personality disorder (BPD), and a nonclinical control group. Findings showed that all clinical groups differed from controls with respect to their overall emotional intelligence score, which dovetails with previous findings from self-report measures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
63
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 49 publications
11
63
0
5
Order By: Relevance
“…This result coincides with others EI studies in the field of psychopathology [17][18][19] and with previous empirical research that suggests that individuals with GAD show more heightened intensity of emotions, expressing negative, but not positive, moods more often, report more frequently negative reaction to self-emotions, and more difficulty in managing them [21]. Despite our preliminary evidence on the predictive value of the deficits in EI in relation to GAD, certain limitations need to be addressed in further research.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result coincides with others EI studies in the field of psychopathology [17][18][19] and with previous empirical research that suggests that individuals with GAD show more heightened intensity of emotions, expressing negative, but not positive, moods more often, report more frequently negative reaction to self-emotions, and more difficulty in managing them [21]. Despite our preliminary evidence on the predictive value of the deficits in EI in relation to GAD, certain limitations need to be addressed in further research.…”
Section: Discussionsupporting
confidence: 91%
“…Hertel and colleagues [19] found that it is possible to discriminate between the different clinical groups based on their levels of EI, specifically emotional understanding. These results also showed significant differences in EI between patients with different mental disorders.…”
mentioning
confidence: 98%
“…Specifically, the borderline patients were reduced in their ability to understand emotional information and to regulate emotions, but they performed as well as the nonclinical controls in perceiving emotions and using emotions to facilitate thought. In contrast to Beblo et al (2010), Hertel et al (2009) did not control for general intelligence and therefore the reduced emotional intelligence performance of the BPD patients may be attributable to group differences in cognitive ability. Variation in borderline symptom severity may also differentially affect emotional intelligence ability in these two studies, but there is insufficient data to evaluate this claim.…”
Section: Emotional Intelligencementioning
confidence: 79%
“…Assays of emotional intelligence suggested enhanced, reduced, or conserved abilities in borderline subjects (Beblo et al, 2010;Hertel et al, 2009;Park et al, 1992). This variation in reported emotional intelligence may vary, in part, as a function of borderline symptom severity or overall cognitive ability.…”
Section: Discussionmentioning
confidence: 91%
“…Another limitation relates to how EI levels, as measured by TMMS, reflect actual individual traits. The validity of EI measured by self-report might be undermined by self-enhancement, faking and limited self-insight [49] . As mentioned previously, there is also an ability model of EI.…”
Section: Discussionmentioning
confidence: 99%